Persistence of Stains and DNA on Evidence in Hostile Situations - Piters Alice; Esponda Audrey; Beaufils Martine; Monique Guillaume; Doutremepuich Antoine; Doutremepuich Christian (Forensic Science Today - Peertechz Publications, 2016)
In order to exploit DNA evidence, biological liquid must be detected and recovered. It has been suggested that some hostile conditions like a long water soaking period may have an influence on evidence recovery and thus results and interpretation. These researches demonstrate that adapting a protocol for each situation allows to recover any evidence. It still possible to detect and identify blood stain after a washing machine even at 90°C. For semen stain, detection is not possible due to the elimination of the acid phosphatase, but spermatozoa can persist on clothes and a DNA profile can be obtained. Contact cells can be recovered on support which has been immerged in water even several weeks or in contact with fire extinguisher powder or liquid. This study shown that if cells dry enough time to adhere to the support (>1 hour) before water immersion, it is possible to obtain a DNA profile.